Amyloid-β, p-tau and reactive microglia are pathological correlates of MRI cortical atrophy in Alzheimer's disease. Issue 4 (24th November 2021) - Frigerio, Irene; Boon, Baayla D C; Lin, Chen-Pei; Galis-de Graaf, Yvon; Bol, John; Preziosa, Paolo; Twisk, Jos; Barkhof, Frederik; Hoozemans, Jeroen J M; Bouwman, Femke H; Rozemuller, Annemieke J M; van de Berg, Wilma D J; et al.
Abstract: Alzheimer's disease is characterized by cortical atrophy on MRI and abnormal depositions of amyloid-beta, phosphorylated-tau and inflammation pathologically. However, the relative contribution of these pathological hallmarks to cortical atrophy, a widely used MRI biomarker in Alzheimer's disease, is yet to be defined. Therefore, the aim of this study was to identify the histopathological correlates of MRI cortical atrophy in Alzheimer's disease donors, and its typical amnestic and atypical non-amnestic phenotypes. Nineteen Alzheimer's disease (of which 10 typical and 9 atypical) and 10 non-neurological control brain donors underwent post-mortem in situ 3T 3D-T1, from which cortical thickness was calculated with Freesurfer. Upon subsequent autopsy, 12 cortical brain regions from the right hemisphere and 9 from the left hemisphere were dissected and immunostained for amyloid-beta, phosphorylated-tau and reactive microglia, and percentage area load was calculated for each marker using ImageJ. In addition, post-mortem MRI was compared to ante-mortem MRI of the same Alzheimer's disease donors when available. MRI-pathology associations were assessed using linear mixed models. Higher amyloid-beta load weakly correlated with higher cortical thickness globally ( r = 0.22, P = 0.022). Phosphorylated-tau strongly correlated with cortical atrophy in temporal and frontal regions (−0.76 < r < −1.00, all P < 0.05). Reactive microglia load strongly correlated with cortical atrophy in the parietal region ( r = −0.94, P < 0.001). Moreover, post-mortem MRI scans showed high concordance with ante-mortem scans acquired <1 year before death. In conclusion, distinct histopathological markers differently correlated with cortical atrophy, highlighting their different roles in the neurodegenerative process, and therefore contributing to the understanding of the pathological underpinnings of MRI atrophic patterns in Alzheimer's disease. In our cohort, no or only subtle differences were found in MRI-pathology associations in Alzheimer's disease phenotypes, indicating that the histopathological correlates of cortical atrophy in typical and atypical phenotypes might be similar. Moreover, we show that post-mortem in situ MRI can be used as proxy for ante-mortem in vivo MRI. Abstract : Frigerio et al. report that in Alzheimer's disease, amyloid-beta, phosphorylated-tau and reactive microglia load measured with immunohistochemistry, are important correlates of MRI cortical atrophy, acquired both ante-mortem in vivo and post-mortem in situ . In summary, distinct histopathological markers differently correlate with cortical atrophy, highlighting their different roles in the neurodegeneration process. Graphical Abstract: